GENDANG AGONG DALAM PERTUNJUKAN KUNTAU DI KABUPATEN PASER KALIMANTAN TIMUR - Aris Setyoko; Zamrud Whidas Pratama; Pazru Rahman (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2023)
This study discusses working on the music of Gendang Agong in the Kuntau performance in Paser Regency, East Kalimantan. Gendang Agong is a traditional musical ensemble based on one of its functions used to accompany Kuntau performances, namely the martial arts or pencak silat traditions of the Paser Tribe. The study of the concept of garap karawitan Rahayu Supanggah related to the material for working on, cultivating, working on equipment, working on furniture/equipment for garap, determining the garap, and consideration on garap is used to analyze it. This research is a qualitative research with analytical descriptive research method. The results of the study show that the garap of Gendang Agong music has a working concept that applies in karawitan scholarship. The material for Gendang Agong is in the form of a transcript of musical notation by writing kepatihan notation with slendro pathet manyura. Cultivators are musicians who have a cultural background as the influence of virtuosity. The working facilities are in the form of quality musical instrument organology to support maximum sound. Furniture/cultivation tools, namely tools/software in the form of musicians' musical ideas that are formed based on their background as the casting of musical practice. The determining factor for garap is in the form of signs for musicians when working on it based on function, namely as an accompaniment for Kuntau. The consideration of working on it is musicians who are ready and responsive to emergencies for creativity when faced with an unsupportive performance venue. The series of six concepts worked on by supanggah is a unified whole that supports each other in forming traditional music compositions to build a musical atmosphere to accompany the Kuntau Paser performance.